Analysis of the Contribution of Land and Building Tax to the Development of Namara Village, Aru Tengah Sub-District, Aru Islands District, 2022 - Aprilia Kamsy; Ibnu Fajarudin (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to answer questions regarding the contribution of Land and Building Tax to the development of Namara Village, Procedures for collecting Land and Building Tax, Distribution of balances and Allocation of Land and Building Tax Collection Results. This research is located in Namara Village, Aru Tengah District, Aru Islands Regency, Maluku. This research is a type of qualitative research that is descriptive in nature. The research data includes primary data, namely data obtained directly from the results of interviews with informants and secondary in the form of data or information in the form of evidence, records or historical archival reports regarding the details of the 2022 land and building tax revenue. The results of the study show that the contribution of land and building tax in 2022 has increased well, this is evidenced by the many developments carried out by the village government and the very high level of compliance by the village community in paying taxes.